ETNOMATEMATIKA PADA LAYANGAN SENDAREN DI MASYARAKAT KECAMATAN LAKBOK - Kirana Sumarman, Indah; Nurjamil, Dedi; Yulianto, Eko (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
This study examines ethnomathematics in the context of the traditional kite game Layangan Sendaren in Lakbok District, Ciamis Regency, West Java. Using a qualitative ethnographic approach, the research identifies mathematical activities involved in the process of making Layangan Sendaren, such as counting, locating, measuring, designing, playing, and explaining. These activities align with the theory of mathematical activities proposed by Bishop and encompass various aspects of informal mathematics practised by artisans. Additionally, the study reveals the philosophical values embedded in the Layangan Sendaren game, including solidarity, innovation, and cooperation, which serve as symbols of community unity and a cultural educational medium for younger generations. Layangan Sendaren is not merely a game but also a form of cultural heritage that reflects the collective efforts of the community in protecting agricultural fields through the sounds it generates to repel pests. The findings of this study are expected to contribute to the development of culturally based teaching materials and to enhance the understanding of ethnomathematics concepts in everyday practices.